Uptake of internet-delivered UK adult hearing assessment. (2nd November 2021) - Dawes, Piers; Munro, Kevin J.; Frank, Timothy L.; Moore, David R.; Armitage, Chris; Marsden, Antonia; Lees, Jane; Dillon, Harvey
Abstract: Objective: To evaluate uptake of the internet-based hearing test, with respect to the 11% of UK adults that have hearing loss but do not use hearing aids. Design: Feasibility study in a primary care practice in the North of England. Study Sample: Adults aged 50–74 years were sent postal invitations to complete an internet hearing test ( N  = 600). Those who completed the test, those who failed (>35 dB HL in the better ear) and demographic correlates (age, gender, ethnicity and socioeconomic level) were recorded. Results: 11.2% of invited adults completed the hearing test and 7.7% failed it. Those who took the test tended to have a higher socioeconomic background than those who did not. There were no differences in age, ethnicity or gender between those who took the test and those who did not. Conclusions: An estimated 70% (7.7%/11.0%) of adults with hearing loss but who do not use hearing aids took the test. Uptake was equitable across most demographic categories. Uptake was high among a study sample that was substantially more deprived than the general UK population. Internet-based hearing testing offers an efficient paradigm for identifying hearing loss.